2012
DOI: 10.1007/s10336-012-0814-6
|View full text |Cite
|
Sign up to set email alerts
|

Flight speeds of migrating seabirds in the Strait of Gibraltar and their relation to wind

Abstract: Wind is an important selective agent in bird migration. In this study, we investigated the influence of wind on the air speed of pelagic seabirds in the Strait of Gibraltar by means of radar measurements. The birds were identified visually at the species level. A total of 354 radar tracks of migrating birds were analysed, with an average tracking time of 147 s per target. An interspecific comparison under negligible wind speeds showed a slight increase of air speed in the order from Cory's Shearwater, a typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…As we predicted in our hypotheses, the capacity to adapt the flight pattern to wind conditions can be constrained by flight type and morphological characteristics of the different species. Mateos-Rodríguez and Bruderer [45], for the same range of species as in our study, showed that these species responded differently to the wind in terms of airspeeds, depending on their morphological characteristics and flight behaviour. In the same way, morphological parameters and flight type could determine seabirds' directional behaviour.…”
Section: The Case Of a Gliding Speciessupporting
confidence: 73%
“…As we predicted in our hypotheses, the capacity to adapt the flight pattern to wind conditions can be constrained by flight type and morphological characteristics of the different species. Mateos-Rodríguez and Bruderer [45], for the same range of species as in our study, showed that these species responded differently to the wind in terms of airspeeds, depending on their morphological characteristics and flight behaviour. In the same way, morphological parameters and flight type could determine seabirds' directional behaviour.…”
Section: The Case Of a Gliding Speciessupporting
confidence: 73%
“…Numerous studies have shown that migrants using flapping flight increase their airspeed in headwinds, however analysis and interpretation is occasionally hampered by the method used to quantify supporting winds (Shamoun-Baranes et al 2007 ). Coastal observations indicate seabirds mostly decrease airspeed with tailwinds and increase airspeed in headwinds, similar to landbirds (Mateos-Rodríguez and Bruderer 2012 ). Biologging has shown that during sea crossings, lesser black-backed gulls Larus fuscus increase their airspeed during flapping flight in headwinds and cross winds, but still fly slower than optimal for minimizing energy expenditure (McLaren et al 2016 ).…”
Section: Individual Responsementioning
confidence: 69%
“…Observation of the combined nocturnal bird stream confirmed that airspeed was faster under headwinds and slower under tailwinds (Bloch & Bruderer 1982, Liechti 1995, Hedenström et al 2002, Nilsson et al 2014. Tracking radar estimates of the speed of particular species were mainly recorded for diurnal migrants identified by telescope or binoculars (Bruderer & Boldt 2001, Mateos & Bruderer 2012, caught and released nocturnal migrants (Griffiths 1970, Bruderer & Boldt 2001; or for free flying birds equipped with radio-transmitters (Cochran & Wikelski 2005, Cochran et al 2008.…”
Section: Introductionmentioning
confidence: 97%